A Justiça Constitucional na concretização dos direitos fundamentais: um estudo sobre o alcance dos novos ideais do constitucionalismo contemporâneo - Branco, Carolina Nobre Castello (2011)
This study aims to evaluate the role of Constitucional Justice in the implementation of Fundamental Rights. To that end, it was established as a starting point the changes brought about by new ideas discussed in contemporary constitutionalism. The increasing concern over the effectiveness of Fundamental Rights and the expansion of the substantive content of the Constitution imposes a more comprehensive role of Constitutional Justice and the need to recast their understanding of the interpretative function. Therefore, this work is divided into three distinct stages. At first, the approach begins on the analysis of the relationship between the State and the Constitution, and its gradual evolution to the formation of constitutional state and thus of contemporary constitutionalism. Then, the study proposes the analysis of the 'new' Constitutional Law, approaching the several terminologies that have been adopted to define the actual moment of changing of the conception of ideas about Constitution and its consequences brought to the Law on the theme of constitutionalization of the law and in seeking the concretization of Fundamental Rights. Finally, the study focuses on the activities of the Constitutional Justice and the identification of its relationship to contemporary constitutionalism in attaining Fundamental Rights